Education on Stock Investment in the Capital Market for Students to Achieve Financial Freedom - Ida Subaida (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Students must be able to independently manage finances well and be responsible for financial decisions made. In addition, students are individuals who tend to face financial problems as a result of having income and are still dependent on their parents. Based on initial observations with several groups of students, they stated that they had not carried out investment activities with various causes including the lack of basic knowledge related to investment, limited funds, and even avoiding risk. It is necessary to determine solutions to the problems that occur in the understanding of stock investment by students in the form of stock education to students in the form of socialization activities and share investment assistance during service activities. This activity will consist of outreach about the importance of investing early on starting from a small but consistent amount of funds adjusted to the funds that can be set aside by students. The goal is that students can be motivated to invest in an affordable way. The results of the service can provide an understanding of the importance of investing in stocks from an early age and provide an understanding that stock investments are not difficult, do not have to have large capital, and the amount of risk can adjust to the perception of each investor. Students as participants in community service activities felt that they got a new understanding of stock investment and some of them began to realize the importance of investing from an early age.